FORMULATION, CHARACTERIZATION, AND TYROSINASE INHIBITORY ASSAYS OF NIACINAMIDE-LOADED NANOPARTICLE GEL AS A SKIN WHITENING AGENT - AHDYANI, RISA; LATIFAH, NOR; SA’ADAH, HAYATUS; FATMASARI, ERLINA; ZAMZANI, IRFAN (International Journal of Applied Pharmaceutics, 2024)
Objective: This research aims to formulate a nanoparticle gel of Niacinamide (N) using Chitosan (C) and Sodium Alginate (SA) and determine its tyrosinase inhibitory activity as a skin whitening. Methods: N nanoparticle was carried out using C (0.01%), SA (0.1%), and Calcium Chloride (CC 0.25 %). N was incorporated into the nanoparticle system by different concentrations in each Formula (F): F1(2.5 %), F2 (5%), F3 (7.5%), and F4 (10%). Each formula was characterized for particle size, Polydispersity Index (PI), and Zeta potential by Zetasizer, entrapment efficiency using Spectrophotometer Uv-Vis, and molecular structure using Fourrier Transform Infrared (FTIR). Then, Hydroxy Propyl Methyl Cellulose (HPMC) was incorporated to form a nanoparticle gel of N. N-loaded nanoparticle gel was determined tyrosinase inhibitory using L-tyrosine to obtain Inhibitory Concentration of 50 (IC50) value. Furthermore, data was analyzed using one-way ANOVA (p-value<0.05). Results: The particle size, PI, Zeta potential, and entrapment efficiency obtained for all formulations were found to be F1 (217±7.21 nm, 0.49±0.0521,+8.24±1.75 mV, and 61.22±2.88 %); F2 (225±11.37 nm, 0.51±0.0246,+9.12± 1.97 mV, and 64.01±4.12%); F3 (289±15.26 nm, 0.26±0.0152,+10.55± 1.56 mV, and 68.71±3.86 %); F4 (428±9.44 nm, 0.38±0.0347, 12.33±1.80 mV, and 72.59±3.01%) respectively. The result of FTIR spectra indicated N-loaded in the nanoparticles system. Tyrosinase inhibitory activity of N-loaded gel nanoparticles obtained IC50 99.9775, 73.5605, 52.7187, and 42.3145 μg/ml, respectively. Conclusion: N-loaded nanoparticle gel was successfully prepared and could be a promising candidate for skin whitening agent.